2021
DOI: 10.3389/fphar.2021.748993
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Inflammatory Response–Related Genes, and Prognosis and Immune Infiltration in Patients With Low-Grade Glioma

Abstract: Background: Although low-grade glioma (LGG) has a good prognosis, it is prone to malignant transformation into high-grade glioma. It has been confirmed that the characteristics of inflammatory factors and immune microenvironment are closely related to the occurrence and development of tumors. It is necessary to clarify the role of inflammatory genes and immune infiltration in LGG.Methods: We downloaded the transcriptome gene expression data and corresponding clinical data of LGG patients from the TCGA and GTEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…These findings support the role of immunity in the prognosis of anaplastic glioma. Indeed, an immune-response signature was found in the IDHwt high-risk group and was correlated with a poor prognosis for LGG patients [ 35 ]. Recently, Song et al identified a 120-gene immune infiltration signature differentially expressed in low-grade glioma, compared with the normal brain, and selected a 20-gene immune infiltration signature that could predict the survival of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the role of immunity in the prognosis of anaplastic glioma. Indeed, an immune-response signature was found in the IDHwt high-risk group and was correlated with a poor prognosis for LGG patients [ 35 ]. Recently, Song et al identified a 120-gene immune infiltration signature differentially expressed in low-grade glioma, compared with the normal brain, and selected a 20-gene immune infiltration signature that could predict the survival of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade gliomas will typically relapse after initial treatment. Following recurrence, low-grade gliomas can transform into high-grade gliomas ( 6 8 ). The incidence of glioma accounts for ~40% of all malignancies in the central nervous system tumors, which is highly invasive and infiltrative ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, genes related to inflammation, energy metabolism, autophagy and DNA methylation have previously been reported as prognostic markers of glioma. 10 14 Furthermore, various genetic alterations, such as mutations in the IDH1 , IDH2 and P53 genes, altered expression of epidermal growth factor receptor and aberrant MGMT promoter methylation status, have been reported in gliomas. 15 – 19…”
Section: Introductionmentioning
confidence: 99%
“…For example, genes related to inflammation, energy metabolism, autophagy and DNA methylation have previously been reported as prognostic markers of glioma. [10][11][12][13][14] Furthermore, various genetic alterations, such as mutations in the IDH1, IDH2 and P53 genes, altered expression of epidermal growth factor receptor and aberrant MGMT promoter methylation status, have been reported in gliomas. [15][16][17][18][19] G-protein-coupled receptors (GPCRs), a family of membrane receptors, play an important role in cellular signalling involving ligands, hormones, neurotransmitters and proteases.…”
Section: Introductionmentioning
confidence: 99%